Given is the following QCQP problem: \begin{align} &&\min_{\mathbf{x} \in \mathbb{C}^n} &\|A \mathbf{x} - \mathbf{b}\|^2,\tag{1}\label{1}\\ \text{ subject to:}&&&\\ &&\|\mathbf{x}\|^2 &\leq \alpha^2,\tag{C1}\label{C1}\\ &&\mathbf{c}^{\dagger} \mathbf{x} &= \gamma,\tag{C2}\label{C2} \end{align} with:

  • $A \in \mathbb{C}^{m\times n}$, with $m, n \in \mathbb{N}: m \geq n$: $\ A^{\dagger} A$ positive definite,
  • $\mathbf{b} \in \mathbb{C}^m,\mathbf{c} \in \mathbb{C}^n: 0< \|\mathbf{c}\| < \infty$,
  • $\gamma \in \mathbb{C}: |\gamma| < \infty,\, \alpha \in \mathbb{R}: |\gamma|^2/\|\mathbf{c}\|^2 \leq \alpha^2 < \infty$,
  • $\|.\|$ - $2$-norm,
  • ${}^\dagger$ - Hermitian adjoint, the combined operation of complex conjugation and transposition.

Obviously, there exists no solution for $\alpha^2 < |\gamma|^2/\|\mathbf{c}\|^2$. For the solution of the only norm constraint problem, i.e. without the constraint \eqref{C2}, see here and here.

With the definitions $f(\mathbf{x}):=\|A \mathbf{x} - \mathbf{b}\|^2$, $h(\mathbf{x}):=\mathbf{c}^{\dagger}\mathbf{x} - \gamma$ and $g(\mathbf{x}):=\|\mathbf{x}\|^2 - \alpha^2$, we can write the problem in the standard form: \begin{align} &&\min_{\mathbf{x} \in \mathbb{C}^n} &f(\mathbf{x}),\tag{1}\label{1a}\\ \text{ subject to:}&&&\\ &&g(\mathbf{x}) &\leq 0,\tag{C1}\label{C2a}\\ &&h(\mathbf{x})& = 0.\tag{C2}\label{C1a} \end{align}

The Lagrangian is given by $$L(\mathbf{x},\mu, \lambda) = f(\mathbf{x}) + \mu g(\mathbf{x}) + \lambda h(\mathbf{x}),\tag{2}\label{2}$$ with $(\mu, \lambda)$ KKT-multipliers. In the following we abbreviate $\mathbf{y}:=A^{\dagger}\mathbf{b}$ and denote with $I$ the $n\times n $ identity and with $\mathbf{0}$ a length $n$ column vector with all zero entries.
Solving the linear matrix equation $$ \begin{pmatrix} A^{\dagger}A + \mu I & \mathbf{c}\\ \mathbf{c}^{\dagger} & 0 \end{pmatrix} \begin{pmatrix} \mathbf{x}(\mu)\\ \lambda(\mu) \end{pmatrix} = \begin{pmatrix} \mathbf{y}\\ \gamma \end{pmatrix},\tag{3}\label{3} $$ we obtain the $\mu$-parametric solution $$ \mathbf{x}(\mu) = \begin{pmatrix} I &\mathbf{0} \end{pmatrix} \begin{pmatrix} A^{\dagger}A + \mu I & \mathbf{c}\\ \mathbf{c}^{\dagger} & 0 \end{pmatrix}^{-1} \begin{pmatrix} \mathbf{y}\\ \gamma \end{pmatrix}.\tag{4}\label{4} $$ Using the formula for block matrix inversion, $$ \begin{pmatrix} G & \mathbf{v}\\ \mathbf{v}^{\dagger} &0 \end{pmatrix}^{-1} = \begin{pmatrix} G^{-1} - \frac{G^{-1}\mathbf{v}\mathbf{v}^{\dagger}G^{-1}}{\mathbf{v}^{\dagger}G^{-1}\mathbf{v}} & \frac{G^{-1}\mathbf{v}}{\mathbf{v}^{\dagger}G^{-1}\mathbf{v}}\\ \frac{\mathbf{v}^{\dagger} G^{-1}}{\mathbf{v}^{\dagger}G^{-1}\mathbf{v}} & -\frac{1}{\mathbf{v}^{\dagger}G^{-1}\mathbf{v}} \end{pmatrix},\tag{5}\label{5} $$ an explicit expression for the $\mu$-parametric solution can be written as $$ \mathbf{x}(\mu) = (A^{\dagger}A + \mu I)^{-1}\left(\mathbf{y} - w(\mu)\mathbf{c}\right),\tag{6}\label{6} $$ where $$ w(\mu):=\frac{\mathbf{c}^{\dagger} (A^{\dagger}A + \mu I)^{-1} \mathbf{y} - \gamma}{\mathbf{c}^{\dagger} (A^{\dagger}A + \mu I)^{-1}\mathbf{c}}.\tag{7}\label{7} $$ The solution of \eqref{6} fulfills \eqref{C2}. The remaining task is to find $\mu^*$: $$ f(\mathbf{x}(\mu^*)) = \min_{\mu:\, g(\mathbf{x}(\mu)) \leq 0} f(\mathbf{x}(\mu)).\tag{8}\label{8} $$


(Q1) Is $\|\mathbf{x}(\mu)\|^2$ monotonically decreasing with increasing $|\mu|$?

(Q2) Is $\mu^* \geq 0$?

(Q3) Is $\mu^* = \inf\, \{\mu \geq 0 \mid g(\mathbf{x}(\mu)) \leq 0\}$?




$\|\mathbf{x}(\mu)\|^2$ is monotonically decreasing without jump discontinuities for $\mu \geq 0$ with $\lim_{\mu \to \infty}\|\mathbf{x}(\mu)\|^2 = |\gamma|^2/\|\mathbf{c}\|^2$. If for a fixed $\mu: 0 \leq \mu < \infty$ the solution is $\mathbf{x}^* = \gamma \mathbf{c} /\|\mathbf{c}\|^2$, then this is the solution for all non-negative values of $\mu$. For $\mu <0$ monotonicity holds not on the whole domain of negative real numbers and jump discontinuities can appear.


Yes, see below.


Yes and the global optimal solution is given by $\mathbf{x}^* = \mathbf{x}(\mu^*)$, with $\mathbf{x}(\mu)$ from (6). Although this solution also holds for the case $\alpha^2 = |\gamma|^2/\|\mathbf{c}\|^2$, where the only allowed solution is the one for $\mu \to \infty$, in practice no limit must be taken due to the fact that the solution is already determined to be $\mathbf{x}^* = \gamma \mathbf{c} /\|\mathbf{c}\|^2$.

Strategy for numerical solution

For $\alpha^2 = |\gamma|^2/\|\mathbf{c}\|^2$, no calculation is necessary since the only allowed solution is $\mathbf{x}^* = \gamma \mathbf{c} /\|\mathbf{c}\|^2$.
For $\alpha^2 > |\gamma|^2/\|\mathbf{c}\|^2$, the numerical procedure to calculate the optimal solution simplifies with the help of the answers of (Q1) and (Q2) to calculate $\mathbf{x}(\mu)$ according to (6), starting with $\mu=0$ and increase $\mu$ until (C1) holds.
No solution exists obviously for $\alpha^2 < |\gamma|^2/\|\mathbf{c}\|^2$.



We first investigate the asymptotic solution for large $\mu$. As a first step we divide the first row of (3) by $\mu$: $$ \left(A^{\dagger} A/\mu + I\right) \mathbf{x}(\mu) + \mathbf{c} \lambda(\mu)/\mu = \mathbf{y}/\mu.\tag{A1}\label{A1} $$ Multiplying \eqref{A1} from the left with $\mathbf{c}^{\dagger}$ and using both, the constraint (C2) and the fact that we look for solutions with bounded norm only, we obtain the asymptotic expression $$ \lim_{\mu \to \infty}\lambda(\mu)/\mu = -\gamma/\|\mathbf{c}\|^2\tag{A2}.\label{A2} $$ With \eqref{A2} in the asymptotic limit of \eqref{A1}, we find $$ \lim_{\mu \to \infty} \mathbf{x}(\mu) = \gamma \mathbf{c} /\|\mathbf{c}\|^2=:\mathbf{x}_{\infty},\tag{A3}\label{A3} $$ and thus $$ \lim_{\mu \to \infty} \|\mathbf{x}(\mu)\|^2 = |\gamma|^2/\|\mathbf{c}\|^2.\tag{A4}\label{A4} $$ To investigate the monotonicity of $\|\mathbf{x}(\mu)\|^2$ we start with differentiating (3) w.r.t. $\mu$: The first row yields $$ \mathbf{x}(\mu) + (A^{\dagger}A + \mu I) \mathbf{x}'(\mu) + \mathbf{c}\lambda'(\mu) = 0,\tag{A5}\label{A5} $$ and the second row the trivial condition $\mathbf{c}^{\dagger} \mathbf{x}'(\mu) = 0$. We use for the function derivative w.r.t. $\mu$ the abbreviation $u'(\mu) \equiv \rm{d}\, u(\mu)/\rm{d}\mu$. Multiplying \eqref{A5} with $\mathbf{c}^{\dagger}$ from left we obtain $$ \gamma + \mathbf{c}^{\dagger} A^{\dagger}A\mathbf{x}'(\mu) + \|\mathbf{c}\|^2\lambda'(\mu) = 0,\tag{A6}\label{A6} $$ which yields $$ \lambda'(\mu) = -\dfrac{ \gamma + \mathbf{c}^{\dagger}A^{\dagger}A \mathbf{x}'(\mu)}{\|\mathbf{c}\|^2}.\tag{A7}\label{A7} $$ Using \eqref{A7} in \eqref{A5} we get a conditional equation for $\mathbf{x}'(\mu)$: $$ \left(\left(I - \dfrac{\mathbf{c}\mathbf{c}^{\dagger}}{\|\mathbf{c}\|^2}\right)A^{\dagger}A + \mu I\right) \mathbf{x}'(\mu) = \frac{\gamma \mathbf{c}}{\|\mathbf{c}\|^2} - \mathbf{x}(\mu).\tag{A8}\label{A8} $$ On the left hand side the orthogonal projector $P:=I - \mathbf{c}\mathbf{c}^{\dagger}/\|\mathbf{c}\|^2$ appears that maps elements of $\mathbb{C}^n$ to $\mathcal{U} = \{\mathbf{x} \in \mathbb{C}^n \mid \mathbf{c}^{\dagger}\mathbf{x} = 0\}\subset \mathbb{C}^n$, the subspace orthogonal to the one-dimensional subspace along $\mathbf{c}$. Multiplying \eqref{A8} with $P$ from left we get: $$ \left(PA^{\dagger}A + \mu P \right) \mathbf{x}'(\mu) = -P\mathbf{x}(\mu).\tag{A9}\label{A9} $$ Since $\mathbf{c}^{\dagger} \mathbf{x}'(\mu) = 0$, which is equivalent to $P\mathbf{x}'(\mu) = \mathbf{x}'(\mu)$, we can further write $$ \left(PA^{\dagger}AP + \mu P \right) \mathbf{x}'(\mu) = -P\mathbf{x}(\mu),\tag{A10}\label{A10} $$ which is a linear equation on $\mathcal{U}$ only that completely determines $\mathbf{x}'(\mu)$. We expand \eqref{A10} in an orthonormal basis of $\mathcal{U}$ and use the following notation: $\mathbf{x}_{\mathcal{U}}(\mu)$, $\mathbf{x}'_{\mathcal{U}}(\mu)$ for the representation of $P\mathbf{x}(\mu)$, $\mathbf{x}'(\mu)$ in $\mathcal{U}$, $I_{\mathcal{U}}$ for the identity in $\mathcal{U}$ and $S_{\mathcal{U}}$ for the representation of $PA^{\dagger}AP$ in $\mathcal{U}$. We can write $$ \mathbf{x}'_{\mathcal{U}} = -\left(S_{\mathcal{U}} + \mu I_{\mathcal{U}}\right)^{-1}\mathbf{x}_{\mathcal{U}}(\mu),\tag{A11}\label{A11} $$ and it follows \begin{align} \frac{\rm{d}}{\rm{d}\mu}\|\mathbf{x}(\mu)\|^2 & = \mathbf{x}'(\mu)^{\dagger}\mathbf{x}(\mu) + \mathbf{x}(\mu)^{\dagger}\mathbf{x}'(\mu)\tag{A12}\label{A12}\\ &=\mathbf{x}'(\mu)^{\dagger}P P \mathbf{x}(\mu) + \mathbf{x}(\mu)^{\dagger}PP\mathbf{x}'(\mu)\\ &=\mathbf{x}_{\mathcal{U}}'(\mu)^{\dagger}\mathbf{x}_{\mathcal{U}}(\mu) + \mathbf{x}_{\mathcal{U}}(\mu)^{\dagger}\mathbf{x}_{\mathcal{U}}'(\mu)\\ &=-2\mathbf{x}_{\mathcal{U}}(\mu)^{\dagger}\left(S_{\mathcal{U}} + \mu I_{\mathcal{U}}\right)^{-1}\mathbf{x}_{\mathcal{U}}(\mu).\tag{A13}\label{A13} \end{align} It can be readily seen from its definition that $S_{\mathcal{U}}$ is positive definite, hence $\left(S_{\mathcal{U}} + \mu I_{\mathcal{U}}\right)^{-1}$ is positive definite for $\mu \geq 0$. Since $A^{\dagger}A$ is also positive definite we obtain from (6) together with (7) that $\mathbf{x}(\mu)$ is not diverging for $\mu\geq 0$. Therefore, from \eqref{A13} we obtain $\frac{\rm{d}}{\rm{d}\mu}\|\mathbf{x}(\mu)\|^2 \leq 0$ for $\mu \geq 0$, that is $\|\mathbf{x}(\mu)\|^2$ is monotonically decreasing without jump discontinuities for $\mu \geq 0$. However, the monotonicity is not strict because $\rm{d}\|\mathbf{x}(\mu)\|^2/\rm{d}\mu$ vanishes when $\mathbf{x}_{\mathcal{U}}(\mu) = 0$. The only solution compatible with both constraints (C1) and (C2) that yields $\mathbf{x}_{\mathcal{U}}(\mu) = 0$ is $\mathbf{x}(\mu) = \gamma\mathbf{c}/\|\mathbf{c}\|^2 = \mathbf{x}_{\infty}$. Since this is also the asymptotic solution from \eqref{A3}, we have $\lim_{\mu \to \infty} \rm{d}\|\mathbf{x}(\mu)\|^2/\rm{d}\mu = 0$. Moreover, if (6) yields $\mathbf{x}_{\infty}$ for $\mu < \infty$, it must be the solution for all $\mu$.

For $\mu < 0$, $\left(S_{\mathcal{U}} + \mu I_{\mathcal{U}}\right)^{-1}$ is not guaranteed to be positive definite and hence monotonicity is not given on the whole domain of negative real numbers. Moreover, jump discontinuities can appear where $\mu$ matches eigenvalues of $A^{\dagger}A$ or $S_{\mathcal{U}}$.


We have to distinguish two cases:

  • $\alpha^2 > |\gamma|^2/\|\mathbf{c}\|^2$:
    With the monotonicity of $\|\mathbf{x}(\mu)\|^2$ for $\mu \geq 0$ and \eqref{A4}, we find a $\mu^\star: g(\mathbf{x}(\mu^\star)) < 0$. Therefore, Slater's condition holds which guarantees strong duality of the convex optimization problem and thus the existence of a KKT-point $(\mathbf{x}^*,\mu^*, \lambda^*)$, where $\mathbf{x}^*$ is a local optimum for the optimization problem and $(\mu^*,\lambda^*)$ for the corresponding dual problem. Due to the convexity and strong duality of the problem the following KKT-conditions are sufficient conditions for the global optimum: \begin{align} g(\mathbf{x}^*) &\leq 0,\tag{A14}\label{A14}\\ h(\mathbf{x}^*) &= 0,\tag{A15}\label{A15}\\ \mu^* &\geq 0,\tag{A16}\label{A16}\\ \mu^*g(\mathbf{x}^*) &= 0.\tag{A17}\label{A17} \end{align} \eqref{A16} answers the question for this case.

  • $\alpha^2 = |\gamma|^2/\|\mathbf{c}\|^2$:
    Slater's condition does not hold, however, the only allowed solution is $\mathbf{x} = \mathbf{x}_{\infty}$, the asymptotic solution. Therefore, we have $\mu^* \to \infty$.

For both cases we get $\mu^* \geq 0$.


For $\mathbf{x}(\mu)$ from (6), \eqref{A15} holds. The remaining task is to find the optimal $\mu^* \geq 0$ such that the remaining KKT-conditions hold. To satisfy \eqref{A17}, we require $\mu^* = 0$ if $g(\mathbf{x}(\mu^*=0)) < 0$ and $\mu^* >0$ otherwise. For the latter case we require $\|\mathbf{x}(\mu^*)\|^2 = \alpha^2$ such that (A14) holds. Due to the fact that $\|\mathbf{x}(\mu)\|^2$ is monotonically decreasing for $\mu \geq 0$, we find $\mu^* = \inf\, \{\mu \geq 0 \mid g(\mathbf{x}(\mu)) \leq 0\}$ and the global optimal solution is given by $\mathbf{x}^* = \mathbf{x}(\mu^*)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.